2020
DOI: 10.1371/journal.pbio.3000623
|View full text |Cite
|
Sign up to set email alerts
|

Haplotype of the astrocytic water channel AQP4 is associated with slow wave energy regulation in human NREM sleep

Abstract: Cerebrospinal fluid (CSF) flow through the brain parenchyma is facilitated by the astrocytic water channel aquaporin 4 (AQP4). Homeostatically regulated electroencephalographic (EEG) slow waves are a hallmark of deep non-rapid eye movement (NREM) sleep and have been implicated in the regulation of parenchymal CSF flow and brain clearance. The human AQP4 gene harbors several single nucleotide polymorphisms (SNPs) associated with AQP4 expression, brain-water homeostasis, and neurodegenerative diseases. To date, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 39 publications
1
35
0
Order By: Relevance
“…While astrocytes have previously been implicated in sleep physiology ( Bellesi et al, 2015 ; Ding et al, 2016 ; Halassa et al, 2009 ; Papouin et al, 2017 ; Petit and Magistretti, 2016 ; Bellesi et al, 2018 ; DiNuzzo and Nedergaard, 2017 ; Bojarskaite et al, 2020 ; Ingiosi et al, 2020 ; Foley et al, 2017 ; Ulv Larsen et al, 2020 ; Frank, 2013 ; Clasadonte et al, 2017 ), we present the first example of an acute in vivo astrocytic manipulation that changes natural sleep. Acute manipulation via chemogenetics was advantageous because DREADD activation mimics endogenous signaling pathways known to be important in astrocyte signaling.…”
Section: Discussionmentioning
confidence: 98%
“…While astrocytes have previously been implicated in sleep physiology ( Bellesi et al, 2015 ; Ding et al, 2016 ; Halassa et al, 2009 ; Papouin et al, 2017 ; Petit and Magistretti, 2016 ; Bellesi et al, 2018 ; DiNuzzo and Nedergaard, 2017 ; Bojarskaite et al, 2020 ; Ingiosi et al, 2020 ; Foley et al, 2017 ; Ulv Larsen et al, 2020 ; Frank, 2013 ; Clasadonte et al, 2017 ), we present the first example of an acute in vivo astrocytic manipulation that changes natural sleep. Acute manipulation via chemogenetics was advantageous because DREADD activation mimics endogenous signaling pathways known to be important in astrocyte signaling.…”
Section: Discussionmentioning
confidence: 98%
“…Adequate sleep, especially deep sleep (NREM III), is a key factor in the functioning of the glymphatic system which accounts for the clearance of metabolic wastes. The effects of sleep on the glymphatic system are mainly dependent on the dynamic alterations of astrocytic function and AQP4 distribution (113,119,155). Significantly, suppressed glymphatic circulation, astrocytic abnormalities, and AQP4 depolarization are consistently reported in mood disorders, providing support for the posited hypothesis.…”
Section: Discussionmentioning
confidence: 80%
“…Surprisingly, the deletion of AQP4 effectively eliminates the circadian rhythm in glymphatic fluid transport (116). A recent genomic study reports that AQP4-haplotype influences sleep homeostasis in NREM sleep and response to prolonged wakefulness (119), providing supporting evidence for the sleepdependent glymphatic pathway. The high polarization of AQP4 in astrocytic endfeet is under the control of the circadian rhythm, and thus, modulates bulk fluid movement, CSF-ISF exchange, and solutes clearance (116).…”
Section: Sleep-dependent Glymphatic Cyclingmentioning
confidence: 98%
“…A cohort study of adult humans showed that genetic variants in the AQP4 genome are related to sleep quality 30 . Another study reported an AQP4 -haplotype associated with distinct modulations of non-rapid eye movement (NREM) sleep 31 . It seems plausible that the regulation of AQP4 expression by BMP signaling, which we uncovered in this study, is involved in the regulation of water and waste clearance and sleep quality.…”
Section: Discussionmentioning
confidence: 99%